Students' Scientific Attitude in Science Learning Using Discovery Learning-Based Environmental Pollution Digital Book - Haning Hasbiyati; Arini Haque; Nirma Iza Afidati (Jurnal Penelitian Pendidikan IPA, 2022)
The composition of the contents of the digital book is adjusted to the syntax of the discovery learning model. The results of the study were to determine the effect on students' scientific attitudes in learning science. The research method is Quasi-Experimental Design using The Posttest-only control group design. The subjects of this study were students of class VII MTs. Maarif Ambulu. Data collection methods are observation methods and questionnaire methods. Data analysis of the scientific attitude observation method used a t-test, student scientific attitude questionnaire method and scientific performance observation method used descriptive analysis. Based on the results of the t-test analysis, it is known that there is an influence on students' scientific attitudes in learning science by using discovery learning based on environmental pollution digital books. Based on the results, the average value of the experimental class was 80.50 with very good criteria and the control class was 69.67 with good criteria